2021
DOI: 10.1298/ptr.e10085
|View full text |Cite
|
Sign up to set email alerts
|

Association between Social Frailty and Sleep Quality among Community-dwelling Older Adults: A Cross-sectional Study

Abstract: We examined the association between social frailty and subjective sleep quality among community-dwelling adults. Methods: This cross-sectional study recruited Japanese adults over the age of 60 years from health check-ups held in a public townhall in a suburban area between 2018 and 2019. Social frailty was evaluated using five criteria (living alone, not visiting friends sometimes, going out less frequently than the last year, not feeling helpful to friends or family, and not talking to someone every day) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Noguchi et al and de Paula Reboucas et al, who conducted a study of 220 community-dwelling older adults in Brazil, also arrived at similar conclusions. Furthermore, in the present study, stronger cognitive function, as indicated by higher MMSE scores, was associated with better sleep quality [ 37 , 45 ]. These findings are similar to those of Liu et al, who identified a correlation between cognitive function and sleep quality among adults over the age of 50 years in China, and Zhou et al, who conducted a study involving 84 older adults with dementia and 92 healthy older adults and discovered a correlation between cognitive function and sleep quality among the older adults with dementia [ 44 , 46 ].…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Noguchi et al and de Paula Reboucas et al, who conducted a study of 220 community-dwelling older adults in Brazil, also arrived at similar conclusions. Furthermore, in the present study, stronger cognitive function, as indicated by higher MMSE scores, was associated with better sleep quality [ 37 , 45 ]. These findings are similar to those of Liu et al, who identified a correlation between cognitive function and sleep quality among adults over the age of 50 years in China, and Zhou et al, who conducted a study involving 84 older adults with dementia and 92 healthy older adults and discovered a correlation between cognitive function and sleep quality among the older adults with dementia [ 44 , 46 ].…”
Section: Discussionmentioning
confidence: 65%
“…Compared with the participants with good sleep quality, the participants with poor sleep quality had a higher average age, lower average ADL and IADL scores, and a higher average GDS score. Noguchi et al studied the associations among physical function, depression, and quality of sleep among 300 community-dwelling older adults with an average age of 73 years in Japan and discovered significant correlations among age, IADL and GDS scores, and sleep quality [ 37 ]. Hsu et al studied sleep problems, depression, health conditions, and physical functions among 400 older adult patients at a hospital clinic in southern Taiwan and identified significant associations among ADL scores, GDS scores, and sleep quality; in that study, compared with the participants with good sleep quality, those with poor sleep quality were generally less educated and had lower MMSE scores [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Social well-being reflects the ability to navigate society, and the extent to which they experience societal belonging, whereas socially-supported sleep underscores quality relationships with close individuals. Social engagement emphasizes community-based activities and interpersonal interactions based on resource sharing (84). Social engagement reflects types of social groups and the frequency of engaging with social groups, rather than close relationships.…”
Section: Related Concepts and Definitionmentioning
confidence: 99%
“…Previous studies have revealed an independent association between frailty and sleep-disordered breathing [4,5]; the relationships between various frailty-related factors (e.g., sarcopenia) and sleep quality or duration have also been investigated [6][7][8]. In Korea, the prevalence of insomnia among community-dwelling older adults is approximately 20%-30% [9,10]; the prevalence of frailty among older adults is approximately 10%-20% less than that of insomnia [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Its phenotype include unintentional weight loss, exhaustion, low physical activity, slowness, and weakness; it is associated with an increased risk of falls, hospitalization, morbidity, and mortality [2]. Sarcopenia is an elementary factor of frailty and is defined as a progressive reduction of mass and strength in the skeletal muscles [3].Previous studies have revealed an independent association between frailty and sleep-disordered breathing [4,5]; the relationships between various frailty-related factors (e.g., sarcopenia) and sleep quality or duration have also been investigated [6][7][8]. In Korea, the prevalence of insomnia among community-dwelling older adults is approximately 20%-30% [9,10]; the prevalence of frailty among older adults is approximately 10%-20% less than that of insomnia [11,12].…”
mentioning
confidence: 99%